Pengaruh Struktur Modal terhadap Pajak Penghasilan dan Ukuran Perusahaan sebagai Moderasi (Effect of Capital Structure on Income Tax and Firm Size as Moderating) - Pega, Eusebius Faleriano; Djuharni, Darti; Liana, Yuyuk; Djafri, Taufik (STIE Malangkucecwara, 2023)
This study aims to measure the effect of capital structure on income tax with company size as a moderating variable. Data was collected from 57 companies in the consumer goods industry sector listed on the Indonesian stock exchange for the 2019-2021 period. Of the 57 companies that met the criteria, there were 14 companies. A number of these 14 companies were then analyzed with the help of SmartPLS and the results obtained were that capital structure had a significant effect on income tax as indicated by the LDAR and DER ratios, company size as a moderating variable also affected the relationship between LDAR and income tax, but company size as a moderating variable did not affect the corporate income tax payable.